KEWENANGAN PERIZINAN DALAM PENGELOLAAN LINGKUNGAN PADA USAHA PERTAMBANGAN - puluhulawa, Fenty U. (Jurnal Legalitas, 2010)
this article describes issues related to licensing in the mining bussines today.in this article will describe the insitution on terms of licensing authority relating to the mining bussines. next will be described several weaknesses in the exiting lincesing system,this article is normative,that is expected weaknesses in the exiting licensing system.this article is normative, that is expected to provide solutions about the need for an integrated institusional system in the management of licensing by licensing an integrated institutional arrangement.with an integrated lincesing system is expected to facilitate the coordination,integration and implemtation oversight Keywords: Authority,Licensing,Environmental Managenrenf,Mining